Machinability evaluation in hard turning of AISI 4340 steel with different cutting tools using statistical techniques - Caydas, U. (Sage Publications Ltd, 2010)
This paper is concerned with the continuous turning of AISI 4340 steels with hardness values in the range between 360 and 460 HV using cubic boron nitride, ceramic, and P10 grade carbide tools. The objective of this paper is to study the performance of these cutting tools and the effect of workpiece hardness on machinability responses. The samples were oil quenched and tempered at 250, 350, and 500 degrees C for 1 h in order to obtain different hardness values. Surface roughness, tool flank wear, maximum tool-chip interface temperature, and microhardness variations after machining are assessed. A Taguchi orthogonal array was used to guide the experiments. Cutting speed, feed rate, depth of cut, workpiece hardness, and tool types were varied in the experiments. A detailed statistical investigation was made by using analysis of variance, Tukey-Kramer comparison, and correlation tests. The best combination of cutting parameters for determining optimal conditions and the influence of each factor on the response were revealed and are discussed in detail.
Keywords: hard turning; statistical analysis; cubic boron nitride tools; AISI 4340 steel